Substansial Kepuasan Konsumen Rumah Makan “Soto Dok Lamongan” Nganjuk - Ratnanto, Sigit Ratnanto; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this study is to find out how the signification of taste, store atmosphere and price affects the consumer satisfaction of Rumah Makan "Soto Dok Lamongan" Nganjuk, either partially or simultaneously. This research uses a quantitative descriptive approach, and the procedure of collecting information using polls, while data analysis techniques with multiple regression analysis methods. The size of the sample in the research was 80 respondents, with the method of sampling using accidental sampling procedures. The results found that Taste and store atmosphere had a significant effect on consumer satisfaction. Price does not have a significant influence on consumer satisfaction. And taste. store atmosphere, and prices simultaneously affect consumer satisfaction. These results show that the management of "Soto Dok Lamongan" Nganjuk restaurant, need to maintain taste, improve store atmosphere, and improve prices.